Impact Of Sand Mining On Sg. Perak River Morphology Using Geographical Information System - Kamaruddin, Nurain Soleha (Universiti Sains Malaysia, 2022)
Mining sand resources from rivers is now prevalent practice, particularly in the state of Perak, and may result in the destruction of public assets as well as repercussions or increased stress on commercial and noncommercial living resources that rely on these places. This study was conducted to estimate the effect of sand mining effect on current Sg. Perak morphology based on on-site fieldwork and spatial analysis. The Acoustic Doppler Current Profiler (ADCP) was utilized to project the river profile in this investigation. The ADCP could swiftly profile vast river cross-sections, enhance data accuracy in sediment transport studies and measure the total discharge of a specific crosssection. The Van Veen Grabber and Helley Smith sediment samplers gather bed soil samples and determine sediment transport. These methods are used to determine the appropriateness of available sand material and the flux of sediment transport on a small scale. The surveys and analysis of the collected data showed that 80% of the grab samples were good-quality sand. In 2020, Pendiat's riverbed eroded between 28.51 m and 36.57 m, while sand was deposited between 11.49 m and 72.76 m. Only three places on Teluk Kepayang indicate erosion ranging from 8.26 to 58.81 meters. The rest data indicate the addition of a riverbank within the range 14.03-m-to-72.53-m. Pendiat's islands are predicted to grow 1 to 9% per month, but Teluk Kepayang's PG island would shrink 5% by March 2020. Pendiat's sandbank is 0.3577 ha to 1.8833 ha, whereas Teluk Kepayang's is 0.7152 ha to 1.1465 ha. The study area's sand mining operations do not meet guidelines. Due to limited sediment movement, river depth, water flow, riverbank erosion, and island enlargement altered the adjacent hydraulic system. The sand company must also provide a bore log profile to calculate how much river sand can be extracted. The pump and Pontoon approach is optimal for sand dredging since it reduces riverbank erosion and maintains water quality. These guidelines and on-site analysis will be used for design evaluation and sediment monitoring removal activities in streams.